The Role of E-Government In Fighting Against The Corruption: A Case Study Of Vietnam - Pham, Thanh Nga (Yayasan Ahmar Cendekia Indonesia, 2020)
Corruption is always a big problem exist in every country. Today, the corruption is not only in the public sector but also in the private sector. Each State has used many ways to prevent and fight this crime. The 4th Industrial Revolution (4IE) brings many innovative solutions for modern life. Especially, e-Government is a great achievement of the 4IE. Base on the e-Government, the policies and regulations of States are transparent. It plays an important role to prevent and fight corruption more effectively. In this paper, the author will analyze the case study of Vietnam on fighting corruption base on the information technology and the outcome of applying e-Government on preventing and fighting corruption in both public sector and private sector. From this result of research, the author will recommend some solutions to improve the corruption status in Vietnam on the next period.